The relationship of attention and memory functions with alcohol consumption in alcohol dependent male patients - Özgür İlhan, İnci and Demirbaş, Hatice and Koçak, Orhan Murat (Journal of Dependence, 2004)
Objective: In the studies done on neuropsychological functions in alcohol dependence, especially memory and executive functions were shown to be disturbed. However, the question of whether such disturbances were present before the development of alcohol dependence or whether they should be considered as complications of alcohol use has not been answered yet. In order to find an answer to this question, attention and memory functions of alcoholdependent male patients were assessed and their relationships with alcohol consumption were investigated in the present study. Method: A total of 32 male alcohol-dependent patients aged 50 years or younger, with at least 5 years of educational history who had gone through no more than 3 weeks of detoxification formed the study population. Beck Depression Inventory, Spielberger State and Trait Anxiety Inventories, Verbal and Nonverbal Cancellation Test (VNCT), Rey Auditory-Verbal Learning (AVLT), Stroop, and WAIS-Block Design Tests were used. Relationships between test scores and time to stereotypical alcohol consumption history were determined. Results: No significant relationships were found between Stroop subscores, Cancellation Test, Block Design Scores, immediate memory, long term memory, highest learning, and recognition scores of AVLT. However, a positive and statistically significant correlation was found between AVLT and time to stereotypical alcohol consumption. Correlations between length of duration of addictive drinking and and time to stereotypical alcohol consumption were determined. Stroop subscores, Cancellation Test efficiency scores, Block Design and AVLT scores (except immediate memory subscore) were not found to be statistically significant. Conclusion: It can be suggested that not all of the components of neuropsychological functions can be related to the direct effects of alcohol. Further studies are needed to define possible effects of neuropsychological functions in the development of alcohol dependence.